2010
DOI: 10.1007/s00044-010-9481-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, anticancer activity, and QSAR-studies of some new tetrahydropyrimidines

Abstract: Several new substituted 1,2,3,4 tetrahydropyrimidine derivatives have been synthesized and evaluated for their in vitro anticancer activity on various cell lines. Some of the molecules have exhibited significantly potent inhibition on several cell lines. To find out inter correlation between anticancer activity and molecular descriptors, QSAR study was carried out. Molecular descriptors used for the study were ClogP (lipophilic), CMR (steric), and polarity (electronic). Anticancer activity is expressed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A positive influence of lipophilic and electronic parameters and a negative influence of steric parameters was observed when descriptors were correlated with anticancer activity against a prostate cancer cell line. The correlation between the activity against the CNS cancer cell line and molecular descriptors showed that decreasing the lipophilicity and electron density while increasing the bulk of the substituent will increase the potency (148).…”
Section: Anticancer Activitymentioning
confidence: 99%
“…A positive influence of lipophilic and electronic parameters and a negative influence of steric parameters was observed when descriptors were correlated with anticancer activity against a prostate cancer cell line. The correlation between the activity against the CNS cancer cell line and molecular descriptors showed that decreasing the lipophilicity and electron density while increasing the bulk of the substituent will increase the potency (148).…”
Section: Anticancer Activitymentioning
confidence: 99%
“…The pyrazolopyrimidines 11a–b were obtained by cyclization of pyrazolones 10a–b with thiourea in refluxing ethanol containing 10% potassium hydroxide (Scheme 2). The formation of pyrazolopyrimidinethione 11 is believed to be formed via initial condensation of thiourea with the carbonyl group of 10 and subsequent elimination of water followed by addition NH 2 of thiourea on the double bond system of 10 [21, 2831]. Pyrazolopyrimidinethiones 11a–b was used as building blocks for the synthesis of condensed heterocycles.…”
Section: Resultsmentioning
confidence: 99%
“…Among the pyrimidine derivatives, pyrimidine carboxamides represent a promising class of bioactive substances and are of particular interest in the medical fields. For instance, 6‐methyl‐4‐aryl‐2‐thioxo‐1,2,3,4‐tetrahydropyrimidine‐5‐carboxamides ( I ) were screened for their anticancer activity . N ‐(substituted phenyl)‐2‐methylthio‐4‐((pyridin‐3‐ylmethyl)amino) pyrimidine‐5‐carboxamides ( II ) have moderate antifungal activities against S. Sclerotiorum .…”
Section: Introductionmentioning
confidence: 99%